STRATEGI PENCAPAIAN PERKEMBANGAN ANAK DI TAMAN KANAK-KANAK DWIJENDRA MATARAM - Rudiarta, I Wayan; Sukerti, I Gusti Ayu; Suary, Ni Putu Chandra Paramis (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This study aims to describe the strategies used in efforts to achieve child development which took place at TK Dwijendra Mataram. The development of children who are the subject of research includes aspects of religious and moral values, physical-motor, cognitive, language, socio-emotional and artistic. Preschool age is a golden age for the growth and development of children. At this golden age a child must be given the right touch to reach the point of maximum development. This research was conducted using a qualitative approach in which the data obtained will be processed and then described in the form of words that describe the results of the study. To test the validity of the data, a triangulation technique was used, which in obtaining the data used the methods of interview, observation and literature study. The results of the study indicate that to achieve the development of religious and moral values, a habituation strategy is used, namely habituation to cultivate a religious and moral culture. Furthermore, on the physical-motor aspect, the teacher uses interactive learning strategies and participatory learning. In the cognitive aspect, the teacher uses a reward strategy, singing method and a Student Center Learning approach. In the language aspect, teachers use mentoring strategies to students to the fullest. Then on the aspect of socio-emotional development, the strategy applied is the fascinating storytelling method. As for the development of the artistic aspect, the school holds extra-curricular activities.